MAMBA’UL ULUM MOJOKERTO ISLAMIC BOARDING SCHOOL RENOVATION MENTORING - Diah Sarasanty; Erna Tri Asmorowati (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2020)
The Mambaul Ulum Islamic boarding school was established in 1958 with the aim of fostering students to become the next generation capable of upholding Islamic teachings in the future, tapping students who are able to play an active role in various fields of life in the midst of society and creating santri who independent, physically and mentally healthy and serving the community for the welfare of the afterlife. To achieve this goal, representative educational facilities are needed to support the learning, teaching, and mentoring process of the students. Supporting facilities that should not be neglected are bathing, washing, and toilet facilities. These facilities must be designed in accordance with applicable standards so that students can avoid diseases that can hinder their learning activities. This community service aims to assist Islamic boarding schools in designing and overseeing the implementation of bathroom renovations in accordance with existing construction standards. So that a clean, safe and comfortable boarding environment is created to facilitate the learning process of the students. The result of this assistance is a planning document for renovating the bathroom of the Mambaul Ulum Islamic boarding school and assistance in supervising its construction work.